Purification and properties of glutamate synthase from Thiobacillus thioparus. - Adachi, K (1977)
Glutamate synthase was purified about 250-fold from Thiobacillus thioparus and was characterized. The molecular weight was estimated as 280,000 g/mol. The enzyme showed absorption maxima at 280, 380, and 450 nm and was inhibited by Atebrin, suggesting that T. thioparus glutamate synthase is a flavoprotein. The enzyme activity was also inhibited by iron chelators and thiolbinding agents. The enzyme was specific for reduced nicotinamide adenine dinucleotide phosphate (NADPH) and alpha-ketoglutarate, but L-glutamine was partially replaced by ammonia as the amino donor. The Km values of glutamate synthase for NADPH, alpha-ketoglutarate, and glutamine were 3.0 muM, 50 muM, and 1.1 mM, respectively. The enzyme had a pH optimum between 7.3 and 7.8. Glutamate synthase from T. thioparus was relatively insensitive to feedback inhibition by single amino acids but was sensitive to the combined effects of several amino acids. Enzymes involved in glutamate synthesis in T. thioparus were studied. Glutamine synthetase and glutamate synthase, as well as two glutamate dehydrogenases (NADH and NADPH dependent), were present in this organism. This levels of glutamate synthase and glutamate dehydrogenase were similar in T. thioparus grown on 0.7 or 7.0 mM ammonium sulfate. The sum of the activities of both glutamate dehydrogenases was only 1/25 of that of glutamate synthase under the assay conditions. It was concluded that the glutamine pathway is important for ammonia assimilation in this autotrophic bacterium.